Preparation method of ship antirust coating
By surface modification of nano zinc oxide and graphene nanosheets and encapsulating modified nanocupoles in anti-fouling microcapsules, the problem of copper ion loss in the early stage of traditional coatings is solved, and the long-term ship coating is realized Anti-fouling effect and extended service life.
Patent Information
- Application Number
- CN202411498621.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Traditional anti-fouling and anti-corrosion coatings will lead to a large loss of copper ions in the early stage, making it difficult to achieve long-term anti-fouling and anti-corrosion for ships.
The nano zinc oxide and graphene nanosheets were surface modified by silane coupling agent, and the primer was prepared by combining the base material, and the modified nanocup oxide was wrapped in anti-fouling microcapsules, and mixed with the base material to prepare a top coat. Ultramicro structures are formed to improve hydrophobic capacity.
The long-term anti-fouling effect of the coating is achieved, extending the service life of the coating, and reducing the bioload on the surface of the hull.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating production, in particular to a method for preparing a ship anti-rust coating. Background Art
[0002] The research on anti-corrosion of steel has attracted people's attention more and more. Among various anti-corrosion technologies, coating anti-corrosion technology is the most widely used because it has the characteristics of simple construction, wide adaptability, no restrictions on equipment area and shape, and low cost of recoating and repair. In the marine ship industry, preventing marine biofouling and ship corrosion has always been a big problem. With the rapid development of marine shipping and the continuous development and utilization of marine resources, the harm caused by marine biofouling has become increasingly prominent. Traditional anti-fouling and anti-corrosion coatings use cuprous oxide to inhibit the attachment and growth of marine organisms. When cuprous oxide is directly added to the coating matrix for mixed spraying, the ship coating will produce an "explosive release" phenomenon in the early stage, resulting in a large loss of copper ions in the early stage, and the copper ions released in the later stage are limited, making it difficult to achieve long-term anti-fouling and anti-corrosion of ships. Based on this, a preparation method of ship anti-rust coating is proposed. Summary of the invention
[0003] In order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a ship anti-rust coating, which can achieve a long-term anti-fouling effect of the coating, extend the service life of the coating, and reduce the bioburden on the surface of the hull.
[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing a ship anti-rust coating, comprising the following steps:
[0005] (1) preparing a primer: using a silane coupling agent to perform surface modification treatment on nano zinc oxide and graphene nanosheets, and then mixing them evenly with a base material to obtain a primer;
[0006] (2) Preparation of topcoat: Mix the base material and antifouling microcapsules evenly to obtain the topcoat.
[0007] Preferably, in step (1), the mass ratio of nano zinc oxide to graphene nanosheets is (2-5):1; the nano zinc oxide accounts for 5-10% of the mass of the base material.
[0008] Preferably, in step (2), the antifouling microcapsules account for 10-20% of the mass of the base material.
[0009] Preferably, in step (2), the preparation of the antifouling microcapsules is as follows: S1, surface modification of nano cuprous oxide is performed using a silane coupling agent, and the surface is poured into a 1wt% dodecyl dimethyl benzyl ammonium chloride solution, and the mixture is continuously stirred for 2h, followed by filtering, washing, and drying to obtain modified nano cuprous oxide; S2, Tween-80, methyl silicone oil, and modified nano cuprous oxide are added to deionized water, and mechanical emulsification is performed to obtain an emulsion; S3, the pH of the emulsion is adjusted to 8.5, and urea, 37wt% formaldehyde solution, ammonium chloride, and resorcinol are then added, and the mixture is heated to react at 55°C for 4h, and the pH is then adjusted to 7 to obtain a reaction solution; S4, the reaction solution is cooled, filtered, and dried to obtain the antifouling microcapsules.
[0010] Preferably, in step S1, the mass ratio of nano cuprous oxide to dodecyl dimethyl benzyl ammonium chloride is 5:1.
[0011] Preferably, in steps S2-S3, the mass ratio of Tween-80, methyl silicone oil, modified nano cuprous oxide, urea, 37wt% formaldehyde solution, ammonium chloride and resorcinol is 1:18:18:10:25:1:1; the material-liquid ratio of modified nano cuprous oxide and deionized water is 1:30 g / ml.
[0012] Preferably, in steps (1) and (2), the base material comprises the following raw materials, measured by mass percentage: 0.5-1% of defoamer (YCK-615), 0.2-0.5% of leveling agent (YCK-1330), 0.1-0.5% of dispersant (YCK-2110), 5-10% of petroleum calcium sulfonate, and the remainder is modified polyacrylate copolymer solution.
[0013] Preferably, the modified polyacrylate copolymer solution is prepared as follows: methyl isobutyl ketone is added to a reactor and the temperature is raised to 75° C.; dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate and γ-methacryloxypropyltrimethoxysilane are added to the reactor, azobisisobutyronitrile is added after stirring evenly, and the mixture is kept warm for 3 hours to obtain the product.
[0014] Preferably, the mass ratio of dodecafluoroheptyl methacrylate, γ-methacryloxypropyltrimethoxysilane, glycidyl methacrylate, butyl acrylate, methyl isobutyl ketone and azobisisobutyronitrile is 4:3:12:12:30:0.2.
[0015] The ship antirust paint prepared in the present invention is composed of a primer and a topcoat. When used, the primer is first sprayed on the ship surface, and the topcoat is sprayed on the primer surface after drying, and the drying is continued.
[0016] The present invention provides a method for preparing a ship anti-rust coating, which has the following advantages compared with the prior art:
[0017] Beneficial effects:
[0018] The present invention uses modified nano cuprous oxide and methyl silicone oil as core materials, and wraps urea-formaldehyde resin on the surface as a capsule shell. The antifouling microcapsules formed are evenly distributed in the coating matrix to form an ultra-micron structure. The slowly released silicone oil can improve the hydrophobicity and reduce the navigation resistance of the ship. The gradual rupture of the antifouling microcapsules can slowly release the modified nano cuprous oxide therein, which can prevent the "explosive release" phenomenon of copper, achieve a long-term antifouling effect of the coating, and extend the service life of the coating.
[0019] The present invention uses a silane coupling agent to modify the surface of nano cuprous oxide so that it can be evenly dispersed in a quaternary ammonium salt solution, and the quaternary ammonium salt is combined with the nano cuprous oxide to form a composite antifouling agent, which can further improve the antifouling and sterilization effect to reduce the bioburden on the surface of the hull.
[0020] The coating used in the present invention is composed of a primer and a topcoat. The primer adheres to the ship body to play an anti-rust role, and the topcoat acts on the surface of the primer to form a protective barrier for the primer and simultaneously plays a good anti-fouling role. The combination of the primer and the topcoat improves the anti-rust and anti-fouling effects of the coating. DETAILED DESCRIPTION
[0021] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0022] Example 1
[0023] The preparation of antifouling microcapsules is as follows:
[0024] S1. Surface modification of nano cuprous oxide was performed using silane coupling agent KH560, and the surface was poured into a 1wt% dodecyl dimethyl benzyl ammonium chloride solution, and stirred for 2 hours, followed by filtering, washing, and drying to obtain modified nano cuprous oxide; the mass ratio of nano cuprous oxide to dodecyl dimethyl benzyl ammonium chloride was 5:1.
[0025] S2, adding Tween-80, methyl silicone oil and modified nano cuprous oxide to deionized water, performing mechanical emulsification treatment to obtain an emulsion;
[0026] S3, adjusting the pH of the emulsion to 8.5, then adding urea, 37wt% formaldehyde solution, ammonium chloride and resorcinol, keeping the reaction at 55°C for 4h, and then adjusting the pH to 7 to obtain a reaction solution;
[0027] The mass ratio of the above-mentioned Tween-80, methyl silicone oil, modified nano cuprous oxide, urea, 37wt% formaldehyde solution, ammonium chloride and resorcinol is 1:18:18:10:25:1:1; the material-liquid ratio of modified nano cuprous oxide and deionized water is 1:30g / ml.
[0028] S4, cooling, filtering and drying the reaction solution to obtain antifouling microcapsules.
[0029] Example 2
[0030] The modified polyacrylate copolymer solution is prepared as follows: add methyl isobutyl ketone to the reactor and heat it to 75°C; add dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate and γ-methacryloxypropyl trimethoxysilane to the reactor, stir evenly and then add azobisisobutyronitrile, and keep warm for 3 hours to obtain the modified polyacrylate copolymer solution. The mass ratio of dodecafluoroheptyl methacrylate, γ-methacryloxypropyl trimethoxysilane, glycidyl methacrylate, butyl acrylate, methyl isobutyl ketone and azobisisobutyronitrile is 4:3:12:12:30:0.2.
[0031] Example 3
[0032] A method for preparing a ship anti-rust coating comprises the following steps:
[0033] (1) Preparation of primer: Silane coupling agent KH-550 is used to perform surface modification treatment on nano zinc oxide and graphene nano sheets, and then the mixture is uniformly mixed with a base material to obtain a primer; the mass ratio of nano zinc oxide to graphene nano sheets is 5:1; and the nano zinc oxide accounts for 5% of the base material mass.
[0034] (2) Preparation of topcoat: The base material and the antifouling microcapsules in Example 1 are uniformly mixed, with the antifouling microcapsules accounting for 20% of the base material by weight.
[0035] In terms of mass percentage, the base material includes the following raw materials: 0.5% of YCK-615 defoamer, 0.5% of YCK-1330 leveling agent, 0.1% of YCK-2110 dispersant, 10% of petroleum calcium sulfonate, and the remainder is the modified polyacrylate copolymer solution in Example 2.
[0036] Example 4
[0037] A method for preparing a ship anti-rust coating comprises the following steps:
[0038] (1) Preparation of primer: Silane coupling agent KH-560 is used to perform surface modification treatment on nano zinc oxide and graphene nano sheets, and then the mixture is uniformly mixed with a base material to obtain a primer; the mass ratio of nano zinc oxide to graphene nano sheets is 2:1; and the nano zinc oxide accounts for 10% of the base material mass.
[0039] (2) Preparation of topcoat: The base material and the antifouling microcapsules in Example 1 are uniformly mixed, with the antifouling microcapsules accounting for 10% of the base material by weight.
[0040] In terms of mass percentage, the base material includes the following raw materials: 1% of YCK-615 defoamer, 0.2% of YCK-1330 leveling agent, 0.5% of YCK-2110 dispersant, 5% of petroleum calcium sulfonate, and the remainder is the modified polyacrylate copolymer solution in Example 2.
[0041] Example 5
[0042] A method for preparing a ship anti-rust coating comprises the following steps:
[0043] (1) Preparation of primer: Silane coupling agent KH-570 is used to perform surface modification treatment on nano zinc oxide and graphene nano sheets, and then the mixture is uniformly mixed with a base material to obtain a primer; the mass ratio of nano zinc oxide to graphene nano sheets is 3:1; and the nano zinc oxide accounts for 8% of the base material mass.
[0044] (2) Preparation of topcoat: The base material and the antifouling microcapsules in Example 1 are uniformly mixed, with the antifouling microcapsules accounting for 15% of the base material weight.
[0045] In terms of mass percentage, the base material includes the following raw materials: 0.6% of YCK-615 defoamer, 0.3% of YCK-1330 leveling agent, 0.2% of YCK-2110 dispersant, 8% of petroleum calcium sulfonate, and the remainder is the modified polyacrylate copolymer solution in Example 2.
[0046] Comparative Example 1
[0047] A method for preparing a ship anti-rust coating is basically the same as that of Example 5, except that the anti-fouling capsules in Example 1 are replaced by the modified nano cuprous oxide prepared in Example 1.
[0048] Comparative Example 2
[0049] A method for preparing a ship anti-rust coating is basically the same as that of Example 5, except that the anti-fouling capsules in Example 1 are replaced with untreated nano cuprous oxide.
[0050] Comparative Example 3
[0051] A method for preparing a ship anti-rust paint is provided, wherein a base material and the anti-fouling microcapsules in Example 1 are uniformly mixed, wherein the anti-fouling microcapsules account for 15% of the mass of the base material.
[0052] In terms of mass percentage, the base material includes the following raw materials: 0.6% of YCK-615 defoamer, 0.3% of YCK-1330 leveling agent, 0.2% of YCK-2110 dispersant, 8% of petroleum calcium sulfonate, and the remainder is the modified polyacrylate copolymer solution in Example 2.
[0053] Quality Inspection
[0054] 1. The coatings in Examples 3-5 and Comparative Examples 1-3 were used as samples, and the antifouling performance and water resistance of the samples were tested in accordance with GB / T5370-2007 "Test Method for Shallow Sea Immersion of Antifouling Paint Samples". The test period was 12 months. The specific results are shown in the following table.
[0055] Table 1 Antifouling performance
[0056] category Physical state of topcoat film (%) Biological coverage area (%) <![CDATA[Biomass (g / cm 2 )]]> Example 3 Peeling area 0.35 0.27 0.022 Example 4 Peeling area 0.41 0.56 0.026 Example 5 Peeling area 0.22 0.12 0.017 Comparative Example 1 Spalling area 5.85 4.84 0.106 Comparative Example 2 Spalling area 6.24 7.21 0.143 Comparative Example 3 Peeling area 0.28 0.18 0.019
[0057] It can be seen from the above table that the peeling area of the topcoat in Comparative Example 1-2 is relatively large because the "explosive release" phenomenon occurs in the initial stage, resulting in excessive release of modified nano-cuprous oxide or nano-cuprous oxide, causing more peeling of the topcoat, shortening the service life, and also affecting the later anti-fouling performance.
[0058] 2. Using the coatings in Examples 3-5 and Comparative Examples 1-2 as samples, first spray the primer on the low carbon steel plate and dry it (recorded as the control plate), then spray the topcoat and dry it to obtain the corresponding sample. The drag reduction efficiency of the control plate and each sample was tested using a HAKKE RS6000 rotational rheometer. The specific test results are shown in the following table.
[0059] Table 2 Drag reduction efficiency
[0060]
[0061]
[0062] It can be seen from the above table that the drag reduction efficiency of the samples in comparative example 1-2 is significantly lower than that of the samples in embodiment 3-5, indicating that the use of antifouling microcapsules can greatly improve the drag reduction effect.
[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a ship anti-rust coating, characterized in that: The following steps are included: (1) preparing a primer: using a silane coupling agent to perform surface modification treatment on nano zinc oxide and graphene nanosheets, and then mixing them evenly with a base material to obtain a primer; (2) Preparation of topcoat: Mix the base material and antifouling microcapsules evenly to obtain the topcoat.
2. The method for preparing the ship antirust coating according to claim 1, characterized in that: In step (1), the mass ratio of nano zinc oxide to graphene nanosheets is (2-5):1; the nano zinc oxide accounts for 5-10% of the mass of the base material.
3. The method for preparing the ship antirust coating according to claim 1, characterized in that: In step (2), the antifouling microcapsules account for 10-20% of the base material mass.
4. The method for preparing the ship antirust coating according to claim 1, characterized in that: In step (2), the antifouling microcapsules are prepared as follows: S1. Surface modification of nano cuprous oxide is performed using a silane coupling agent, and the surface is poured into a 1 wt % dodecyl dimethyl benzyl ammonium chloride solution, and stirred for 2 h, followed by filtering, washing, and drying to obtain modified nano cuprous oxide; S2, adding Tween-80, methyl silicone oil and modified nano cuprous oxide to deionized water, performing mechanical emulsification treatment to obtain an emulsion; S3, adjusting the pH of the emulsion to 8.5, then adding urea, 37wt% formaldehyde solution, ammonium chloride and resorcinol, keeping the reaction at 55°C for 4h, and then adjusting the pH to 7 to obtain a reaction solution; S4, cooling, filtering and drying the reaction solution to obtain antifouling microcapsules.
5. The method for preparing the ship antirust coating according to claim 4, characterized in that: In step S1, the mass ratio of nano cuprous oxide to dodecyl dimethyl benzyl ammonium chloride is 5:
1.
6. The method for preparing the ship antirust coating according to claim 4, characterized in that: In steps S2-S3, the mass ratio of Tween-80, methyl silicone oil, modified nano cuprous oxide, urea, 37wt% formaldehyde solution, ammonium chloride and resorcinol is 1:18:18:10:25:1:1; the material-liquid ratio of modified nano cuprous oxide and deionized water is 1:30 g / ml.
7. The method for preparing the ship antirust coating according to claim 1, characterized in that: In steps (1) and (2), the base material includes the following raw materials, by mass percentage: 0.5-1% defoamer, 0.2-0.5% leveling agent, 0.1-0.5% dispersant, 5-10% petroleum calcium sulfonate, and the remainder is modified polyacrylate copolymer solution.
8. The method for preparing the ship antirust coating according to claim 7, characterized in that: The modified polyacrylate copolymer solution is prepared as follows: add methyl isobutyl ketone to the reactor and heat it to 75°C; add dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate and γ-methacryloxypropyltrimethoxysilane to the reactor, stir evenly, add azobisisobutyronitrile, and continue to keep warm for 3 hours to obtain the product.
9. The method for preparing the ship antirust coating according to claim 8, characterized in that: The mass ratio of dodecafluoroheptyl methacrylate, γ-methacryloxypropyltrimethoxysilane, glycidyl methacrylate, butyl acrylate, methyl isobutyl ketone and azobisisobutyronitrile is 4:3:12:12:30:0.
2.
10. An application of the ship antirust coating obtained by the preparation method according to any one of claims 1 to 9, specifically: spraying primer on the ship surface, spraying topcoat on the primer surface after drying, and continuing to dry.
Citation Information
Patent Citations
Surface modification method of cuprous oxide antifouling agent
CN102807774A
Efficient marine antifouling coating and broad-spectrum controlled-release antifouling agent for same
CN102807797A
Anticorrosive and antibacterial coating for upper surface of tank bottom plate of crude oil storage tank and preparation method of anticorrosive and antibacterial coating
CN113652139A
Slow-release cellulose-cuprous oxide antifouling agent as well as preparation method and application thereof
CN116676011A
Anti-fouling Paints & Coatings
US20110070376A1